Cobenefits of global and domestic greenhouse gas emissions for air quality and human health. (April 2017) - West, Jason; Zhang, Yuqiang; Smith, Steven; Silva, Raquel; Bowden, Jared; Naik, Vaishali; Li, Ying; Gilfillan, Dennis; Adelman, Zachariah; Fry, Meridith; Anenberg, Susan; Horowitz, Larry; et al.
Abstract: Background: Reductions in greenhouse gas emissions often reduce emissions of coemitted air pollutants, yielding cobenefits for air quality and human health. Here, we report results of a global cobenefits study—the first to use a global atmospheric model and consistent future scenarios—and results from follow-on studies that downscale those global results to focus on the continental US. Methods: We use the RCP4.5 scenario as an aggressive global greenhouse gas mitigation scenario, and compare it with its associated reference case, the difference between these scenarios is uniquely attributable to the global carbon policy. Findings: In the global study, we find that global greenhouse gas mitigation avoids roughly 0·5 million air pollution-related deaths per year in 2030, 1·3 million air pollution-related deaths per year in 2050, and 2·2 million air pollution-related deaths per year in 2100. Global average cobenefits are US50–380 per ton of CO2 reduced, which exceeds previous estimates. These cobenefits also exceed the marginal abatement costs in 2030 and 2050. Cobenefits here are higher than in previous studies because we account for global air pollution transport, and because of projected population, and baseline mortality growth. We then downscale these results in 2050 to the continental USA to project these cobenefits at fine resolution, using the WRF, SMOKE and CMAQ models, and we separate the contributions of domestic and foreign reductions to US cobenefits. We find that for PM2.5, most of the air quality and health cobenefits are from domestic emissions. By contrast, for ozone, most of the cobenefits results from foreign emissions, including global methane reductions. Interpretation: These results suggest that the air quality and health cobenefits realised by one country will be much greater if foreign countries also reduce greenhouse gas emissions in a coordinated effort. We also conclude that previous studies that focus on domestic or local cobenefits might significantly underestimate the total cobenefits of global greenhouse gas reductions. Funding: US Environmental Protection Agency, the Integrated Assessment Research Program in theUS Department of Energy, Office of Science, theNational Institute of Environmental Health Sciences, thePortuguese Foundation for Science and Technology, and anEPA STAR Graduate Fellowship .